PENGARUH CITRA MEREK, PROMOSI DAN PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN MITRA KIOS UNGGAS PONDOK KOPI - Jeremia Van Der Saar Siallagan; Jamaludin Khalid (LPPM Universitas Asa Indonesia, 2023)
This research aims to determine the influence of brand image, promotion and price perception on customer satisfaction. The population used in the research were business owners who were partners at PT. Poultry Kiosk Partner at Kios Poultry. By using purposive sampling it was determined that the sample size was 100 work partners with the criteria of having collaborated with PT. Poultry Kiosk Partner for more than 1 month. Data collection was carried out through questionnaires to the 100 partners. Linear regression analysis techniques were carried out to determine the correlation between the variables used. The results of the partial t test show that promotions and price perceptions have an effect on customer satisfaction. Meanwhile, the simultaneous F test shows that brand image, promotion and price perception simultaneously influence customer satisfaction with a large influence of 40.1%.